IDENTIFIKASI INDEKS KERENTANAN SEISMIK DI BENDUNGAN BILI-BILI KABUPATEN GOWA DENGAN METODE HORIZONTAL TO VERTICAL SPECTRAL RATIO (HVSR) - Syah, Chairuni; Said L, Muh.; Wahyuni, Ayusari (JFT: Jurnal Fisika dan Terapannya, 2017)
A research has been conducted to determine the value of seismic vulnerability index and vulnerability index mapping at Bili-Bili dam in Gowa district. This research uses seismometer to record seismic wave signal. Data were collected by 9 measurement points. The data obtained is then processed by software Geopsy using the method Horizontal to Vertical Spectral Ratio (HVSR). The result of data processing obtained by the dominant frequency value (f0) and amplification (A0), then calculated seismic susceptibility index value. Based on the result of research indicate that seismic susceptibility index value in Bili-bili Dam area is 0,358-3,884. This indicates that areas in the Bili-Bili Dam include small to medium vulnerability indexes and are still safe in case of an earthquake.